2019
DOI: 10.24042/ajpm.v10i1.3617
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Teacher’s Beliefs and Knowledge about Mathematics

Abstract: This research describes the knowledge and beliefs of pre-service teachers about mathematics. Data collection of this research using written test of 143 mathematics pre-service teachers who have taken six semesters at Universitas PGRI Semarang, and interviewing of three pre-service teachers who are not consistent between knowledge and belief. The data are presented in the form of descriptive quantitative and analyzed qualitatively, including data reduction, data display, and conclusions drawing/verification. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This shows that educators have influenced students' beliefs, as Muhtarom, Juniati, & Siswono (2017b), and Muhtarom, Juniati, Siswono, & Rahmatika (2018) provide illustrations that teachers' beliefs have influenced their students' beliefs. Muhtarom, Juniati, & Siswono (2017b) and Muhtarom, Happy, Nursyahidah, & Casanova (2019) explain that the large number of mathematics prospective teachers have a platonist view, derived from the mathematics experience at school and the lecture program so far that had strengthened his belief. The climber mathematics prospective teacher also confirmed that the beliefs were based on the experience.…”
Section: Discussionmentioning
confidence: 99%
“…This shows that educators have influenced students' beliefs, as Muhtarom, Juniati, & Siswono (2017b), and Muhtarom, Juniati, Siswono, & Rahmatika (2018) provide illustrations that teachers' beliefs have influenced their students' beliefs. Muhtarom, Juniati, & Siswono (2017b) and Muhtarom, Happy, Nursyahidah, & Casanova (2019) explain that the large number of mathematics prospective teachers have a platonist view, derived from the mathematics experience at school and the lecture program so far that had strengthened his belief. The climber mathematics prospective teacher also confirmed that the beliefs were based on the experience.…”
Section: Discussionmentioning
confidence: 99%
“…Teachers must also pay attention to the development of science, technological progress, the conditions of students and the environment as well as the future goals of education, especially the subjects that they teach. As a teacher, it is better if you master Pedagogical Content Knowledge (PCK) which is a category of teacher knowledge that includes knowledge used by teachers in delivering subject matter to students to achieve learning objectives (Alimuddin, Tjakraatmadja & Ghazali, 2020;Muhtarom, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%